2023
DOI: 10.1186/s12860-023-00487-0
|View full text |Cite
|
Sign up to set email alerts
|

BMP9 maintains the phenotype of HTR-8/Svneo trophoblast cells by activating the SDF1/CXCR4 pathway

Xue Yang,
Lingling Ren,
Xiang Chen
et al.

Abstract: Background Bone morphogenetic protein 9 (BMP9) has been shown to regulate processes such as angiogenesis, endothelial dysfunction, and tumorigenesis. However, the role of BMP9 in preeclampsia (PE) is unclear. The purpose of this study was to investigate the role and mechanism of BMP9 in PE. Methods The effects of BMP9 on the viability, migration and invasion of HTR-8/Svneo cells were investigated by CCK-8 assay, wound healing assay and Transwell in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that bone morphogenetic protein 9 (BMP9) regulates the processes involved in endothelial dysfunction ( Long et al, 2015 ). Yang and others ( Yang et al, 2023 ) revealed that serum from PE patients had lower levels of CXCL12 and CXCR4 expression and that there was a positive correlation between BMP9 and these expression levels. In HTR-8/SVneo cells, overexpression of BMP9 increased the levels of CXCL12 and CXCR4.…”
Section: Role Of CXC Chemokines In the Pathogenesis Of Pementioning
confidence: 97%
“…It has been demonstrated that bone morphogenetic protein 9 (BMP9) regulates the processes involved in endothelial dysfunction ( Long et al, 2015 ). Yang and others ( Yang et al, 2023 ) revealed that serum from PE patients had lower levels of CXCL12 and CXCR4 expression and that there was a positive correlation between BMP9 and these expression levels. In HTR-8/SVneo cells, overexpression of BMP9 increased the levels of CXCL12 and CXCR4.…”
Section: Role Of CXC Chemokines In the Pathogenesis Of Pementioning
confidence: 97%